TRIPLE MULTIPLICATIVE THERMORESONANCES ON THE SPECTRA OF EXCHANGE INERTIAL RADIATION GENERATED IN NON-EQUILIBRIUM MEDIA WITH CONTACT GAPS IN ENGINEERING, COSMIC, PSEUDO-ELEMENTARY AND BIOLOGICAL SYSTEMS IN COMPLEX SPACE WITH TRIPLET VIOLATION OF ANTISYMMETRY - ZASPA, YURII (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Calculated ratios that quantitatively describe the properties of resonance triplets of inertial radiation generated in non-equilibrium systems of various scales and levels of organization are given. The multiplicative nature of the energy of resonant components is revealed, which is significantly different from the additive principles of the formation of known triplet structures. The mechanism of triplet violation of the antisymmetry of the complex space is established, which ensures the avoidance of annihilation of the energy created according to the principle of Creatio ex nihilo in the topological contact gaps between the real and imaginary half-spaces. There is a marked dilution of the dominant energy cascades - direct in the imaginary and inverted in the real half-space. The analysis of resonant triads on nuclear and collider spectra was carried out, the components of these spectra were explained and quantitatively calculated. The muon structure of hadrons was confirmed and the parameters of this structure were calculated, as well as the parameters of the collider proton-muon plasma, alternative to the known models of the quark-gluon plasma. The calculation of the spectra of cosmic rays of low, medium, high and ultra-high energies was made, which quantitatively corresponds to natural data. Triple resonances in the spectra of the Sun's radiation and the spectra of solar and geomagnetic activity were detected and quantified. It is shown that the solar spectrum is significantly different from the blackbody spectrum, and the main periods of the Sun's activity are determined by resonant triads on the scale of the heliosphere. Calculated parameters of the cold outer photosphere at the periphery of the Solar System, the background microwave radiation of which is usually erroneously attributed to the account of a "relic" from the so-called Big bang. The analysis of resonant triplets on the spectra of acoustic disturbances in technical systems was carried out. Synchronization of gravitational and electromagnetic modes is noted, which leads to dangerous buffeting modes. The relationship between geodynamic, climatic and biological processes on the planet and the activity of cavitation topological gaps on the periphery of the Solar System has been established. The mechanism of contact capillary thermostabilization of the human body was revealed and the multiplicative triplet coronavirus destruction of this mechanism was noted.
Keywords: triple thermal resonances; principle of multiplicativity; violation of antisymmetry; inertial radiation; non-equilibrium medium; topological discontinuity